R U ready 4 new subtitles? Investigating the potential of social translation practices and creative spellings - Secară, Alina (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
In this paper I investigate novel and creative linguistic features used in non-conventional subtitling settings such as fansubbing, arguing that they can be advantageously used in professional subtitling practices for a specific medium, such as the Internet. The integration of txt lingo in subtitling is supported by the recent explosion of social translation practices as a response to an ever-growing audience fragmentation as well as changes in technology which make the integration of several customised subtitling tracks possible. In an attempt to provide empirical evidence to support this argument I present the initial results of a pilot eye-tracker-based experiment to elicit data on the reception of “unregimented” subtitling when offered as an alternative to conventional subtitling from consumers in selected new subtitling contexts.